1989
DOI: 10.3109/00365548909167446
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Shigella spp. in Childhood Diarrhoea in Iran and Their Antibiotic Resistance

Abstract: The incidence of shigellae was measured in 445 children with diarrhoea in Sanandaj, Kordestan, and 715 in Tehran during a 1-year study. 18 (4%) patients in Sanandaj and 41 (5.7%) patients in Tehran were positive for various shigella species. Sh. boydii (7 strains) and Sh. sonnei (25 strains) were the commonest species in Sanandaj and Tehran respectively. Among the isolates from Sanandaj the highest resistance was to tetracycline (55.5%), whereas in Tehran it was to sulfamethoxazole/trimethoprim (68.3%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
3
3
Order By: Relevance
“…In 2001, 2002, and 2004, S. flexneri was the most common of the four species, whereas in 2003 and from 2005 to 2009, S. sonnei was the dominant species. This finding differs from those of studies conducted in other developing countries (Faruque et al 2002 ; Niyogi and Pazhani 2003 ; Zafar et al 2005 ), where S. flexneri was the most frequently isolated species; however, our results match findings in developed countries (Katouli et al 1989 ; Hale et al 1991 ; Hamamoto et al 2000 ; Bonfiglio et al 2002 ; Ekdaha and Andersson 2005 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In 2001, 2002, and 2004, S. flexneri was the most common of the four species, whereas in 2003 and from 2005 to 2009, S. sonnei was the dominant species. This finding differs from those of studies conducted in other developing countries (Faruque et al 2002 ; Niyogi and Pazhani 2003 ; Zafar et al 2005 ), where S. flexneri was the most frequently isolated species; however, our results match findings in developed countries (Katouli et al 1989 ; Hale et al 1991 ; Hamamoto et al 2000 ; Bonfiglio et al 2002 ; Ekdaha and Andersson 2005 ).…”
Section: Discussioncontrasting
confidence: 99%
“…S. dysenteriae is primarily associated with epidemics of serotype 1 and is associated with the highest fatality rate (5–15%) (Ingersoll et al 2002 ). S. flexneri predominates in areas of endemic infection and is the most frequently isolated species in developing countries (Faruque et al 2002 ; Niyogi and Pazhani 2003 ; Zafar et al 2005 ), and S. sonnei has been implicated in source outbreaks in developed countries (Katouli et al 1989 ; Hale et al 1991 ; Bonfiglio et al 2002 ; Ekdaha and Andersson 2005 ; Hamamoto et al 2000 ). S. boydii is associated with source outbreaks in Central and South America and is rarely isolated in North America (Kalluri et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…14,26 Shigella sonnei was the most prevalent species isolated among Shigella spp. strikingly; this finding differs from other studies in Iran and other developing countries, and matches those from developed countries 19,24 where Shigellosis remains a disease that predominantly affects children. Another relevant enteropathogenic bacterium, Salmonella spp.…”
Section: Discussioncontrasting
confidence: 95%
“…and STEC infections found in this study showed that these organisms are important causes of acute diarrhea in children. 17,19,40 More information is needed, nevertheless, about the sources models of transmission and risk factors of diarrheagenic E. coli infections in Iran especially for the youngest children to implement more efficient control programs on these infections.…”
Section: Discussionmentioning
confidence: 99%
“…This was also true for co-trimoxazole since resistance to this antibiotic increased from 68.3% in 1989 [29], to 70.4% in 2001 [20], 85.6% in 2006 [31] and to 89% in present study. A recent study [33] indicated that 88%, of S. flexneri strains were resistant to this antibiotic that is consistent with our result.…”
Section: Discussionsupporting
confidence: 70%